Services availability and readiness assessment of adolescent sexual and reproductive health in primary healthcare facilities: evidence from selected districts in Ghana - Michel Adurayi Amenah; Jacob Novignon; Ama Pokuaa Fenny; Irene A. Agyepong; Tim Ensor (Reproductive Health)
Abstract Background Globally, adolescent health remains a public health priority given that adolescents often face unique vulnerabilities to health issues like mental disorders, substance abuse, and sexual health risks. In developing countries like Ghana, primary healthcare facilities (PHCs) are often the first point of contact for addressing these issues. However, there is a lack of literature examining the capacity of PHCs to address adolescent sexual and reproductive health (ASRH) issues. This study aims to fill this gap in the literature by assessing the availability and readiness of ASRH services within Ghana’s PHCs. Methods The study utilized a multi-stage sampling approach to select 67 PHCs across four districts in the Greater Accra region, reflecting Ghana's broad demographic diversity. We employed the WHO's Services Availability and Readiness Assessment (SARA) tool to measure the availability and readiness of ASRH services. This framework focused on key domains including service availability and readiness, assessing aspects such as HIV testing, family planning, and availability of contraceptives and necessary staff training. Data analysis was conducted using Stata version 17.0, analysing frequencies and percentages to capture the extent of service provision across the selected facilities. Results The study highlighted significant disparities in the availability and readiness of essential ASRH services (HIV services, family planning, contraceptive pills, IUCD provisions, and male condoms) across selected districts and facility types. In Shai Osudoku, 65% of facilities offered a full range of selected ASRH services, the highest among the districts, whereas Ningo Prampram had the lowest at just 16%. In terms of facility types, 57% of CHPS facilities, 59% of health centres, and 44% of clinics provided all the selected ASRH services. Urban areas reported a 51% provision rate of these services, slightly less than the 54% observed in rural areas. Additionally, readiness disparities were evident: only 21% of urban facilities had adequate service guidelines compared to 29% in rural areas, and a higher percentage of rural facilities (46%) had trained staff, compared to 23% in urban areas. Conclusion This study examined the availability and readiness of ASRH services in PHCs across the Greater Accra region, revealing significant disparities by location and facility type. Particularly, rural and public facilities demonstrated a higher availability of ASRH services compared to urban and private facilities. These findings suggest an uneven distribution of resources and highlight a potential urban underutilization of public health services. Moreover, the study identified a critical lack of service guidelines and trained staff across many facilities, emphasizing the need for enhanced training and resource allocation to improve service readiness. Targeted interventions are necessary to elevate the quality and accessibility of ASRH services, ensuring equitable health care delivery across all regions. Future research should expand to other regions to validate these findings and inform nationwide health strategies.